2001
DOI: 10.1007/s10266-001-8178-z
|View full text |Cite
|
Sign up to set email alerts
|

Cell and tissue behavior on micro-grooved surfaces

Abstract: In this review, we discuss substrates and implant surfaces provided with micrometer-sized groove and ridge patterns. Such "microgrooves" influence cell behavior: the cells align themselves, and migrate guided by the surface grooves. This phenomenon is known as "contact guidance". First, cell structure and cell attachment behavior are described. Then techniques for the production of microgrooves are addressed, and a summary is given of a number of previous in-vitro and in-vivo experiments on this subject. Based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
68
0
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(73 citation statements)
references
References 67 publications
3
68
0
2
Order By: Relevance
“…In addition, the observation of multilayered cells in the multigrooves indicates the production of a large quantity of ECM. The results of this study are supported from the in vivo examinations by Brunette et al 5,23,28 and Walboomers et al 7,22 Brunette et al placed epoxy implants with V-shaped grooves having depths of 22, 10, or 3 m into rat skin and found that the deeper grooved surfaces inhibited epithelial downgrowth. Walboomers et al investigated the in vivo behavior of microgrooved implants in soft tissue of the goat.…”
Section: Discussionsupporting
confidence: 88%
“…In addition, the observation of multilayered cells in the multigrooves indicates the production of a large quantity of ECM. The results of this study are supported from the in vivo examinations by Brunette et al 5,23,28 and Walboomers et al 7,22 Brunette et al placed epoxy implants with V-shaped grooves having depths of 22, 10, or 3 m into rat skin and found that the deeper grooved surfaces inhibited epithelial downgrowth. Walboomers et al investigated the in vivo behavior of microgrooved implants in soft tissue of the goat.…”
Section: Discussionsupporting
confidence: 88%
“…Anisotropic surfaces such as grooved substrata can control cell shape, orientation, division, and the direction of cell migration [Brunette, 1986a;Clark et al, 1990;Oakley and Brunette, 1993;Oakley et al, 1997;Walboomers et al, 1999Walboomers et al, , 2000Walboomers and Jansen, 2001;Dalby et al, 2003;Hamilton et al, 2005a;. This phenomenon is termed topographic or contact guidance [Dunn and Heath, 1976;Brunette, 1986a;Clark et al, 1987Clark et al, , 1990Curtis and Wilkinson, 1998] and is exhibited by a variety of cell populations contacting grooved substrata of various chemical compositions, fabricated by different techniques and having different groove/ridge geometries and dimensions [Brunette et al, 1983;Chehroudi et al, 1988;Clark et al, 1991;den Braber et al, 1995den Braber et al, , 1996Walboomers et al, 1998;Miller et al, 2001;Dalby et al, 2003;Curtis et al, 2005;Evans et al, 2005].…”
Section: Introductionmentioning
confidence: 98%
“…In the leading edge, new cell adhesions are formed, and the actin meshwork contracts, which causes the cell to move in the direction of the new adhesion [Walboomers and Jansen, 2001]. In our study, the surface structures consist of Ti oxide lines with varied width and distance but a common height of only 12 nm.…”
Section: Surface Structure and Cell Orientation: Mechanical Guidance?mentioning
confidence: 99%
“…According to Walboomers and Jansen [2001], precursor contacts precede the formation of a focal contact and are made in two steps: (i) a nonspecifi c approach of the cell membrane to the substrate surface based on electrostatic or much weaker van der Waals forces, and (ii) the specifi c binding via membrane integrin receptors to ECM proteins absorbed on the implant surface. At the interface between Ti ground and the Ti oxide lines, the surface charge density may differ due to varying physicochemical properties of the thin naturally formed oxide fi lm and the thicker thermal-induced oxide lines.…”
Section: Surface Structure and Cell Orientation: Guidance By Surface mentioning
confidence: 99%